If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(-5+4n)-1=-(2n-8)
We move all terms to the left:
-7(-5+4n)-1-(-(2n-8))=0
We add all the numbers together, and all the variables
-7(4n-5)-(-(2n-8))-1=0
We multiply parentheses
-28n-(-(2n-8))+35-1=0
We calculate terms in parentheses: -(-(2n-8)), so:We add all the numbers together, and all the variables
-(2n-8)
We get rid of parentheses
-2n+8
Back to the equation:
-(-2n+8)
-28n-(-2n+8)+34=0
We get rid of parentheses
-28n+2n-8+34=0
We add all the numbers together, and all the variables
-26n+26=0
We move all terms containing n to the left, all other terms to the right
-26n=-26
n=-26/-26
n=1
| 19x+5)=(21x-7) | | 2(y+5)=-2y+2 | | -x-6=x-8-6x-14 | | g+309/22=24 | | -6x+4(x-6)=-10 | | 2-2+26=y | | 3(10+2)=30x+6 | | -(12+9y)+5y=4 | | 13x-6=1+12x | | 2=3y-8 | | q^2+20q-17=0 | | -2=-3v—15v-7v—13v=16 | | x+x-3+x=(6-x)2 | | 62-3x=38 | | x=3/2=48/6 | | 2+19=x | | -3.6=3y-8 | | 2x+4(x)=19 | | 0.4(x+0.45)=9.2 | | 2+5(x)=19 | | 8n-1-6n=-15 | | 7x-3x+-8=24 | | 2(x)=19 | | 2-14+26=y | | 12÷4x=-7 | | 66=6(x+6) | | 3/2n+1/5=2 | | 6(66)=x+6 | | 66-6=x | | n/5+4=29 | | 4+X2+-4x=0 | | -15=w/5 |